(untitled) (Fiep Bulletin - online, 2024)
The comparison of physical capabilities between young futsal and field football players is very important, which brings benefits to young players and a good improvement in physical quality. The research aimed to compare the physical capabilities of young futsal and field football players in the city of Imaculada-PB. It is descriptive research, field research, and a quantitative approach. The sample consisted of young futsal and field football players from the city, and had a sample of 16 players, 5 on the court and 11 on the field, aged between 15 and 18 years old. the PROESP-Br test was applied. The data obtained were analyzed quantitatively, using the Microsoft Excel for Windows 2020 program. The mean and standard deviation of the results of the physical valence tests were, body mass (in kilograms) in football of 64.6±12.8 and in futsal 63.02±8.9; height (in cm) in football 171.9±5.5 and in futsal 171.2±4.3; wingspan (cm) in football 175.1±5 and in futsal 177.4±3.9; waist circumference (in cm) 72.9±9.5 for football and 71.02±7.4 for futsal; sitting and reaching (cm) for football 33.5±6.4 while for futsal 38.2±10.4; abdominal (cm) for football 41.3±10.2 and 41.4±8.2 for futsal; 6 minutes – m 921±138.9 in football and 936.4±147.2 in futsal; long jump (cm) in football 194.9±26.8 and in futsal 226±24; medicine ball throw (cm) 164.4±27.8 for football and 150.8±22 for futsal; in the square (sec.) for football 6.2±1 and 5.5±1.2 for futsal and the 20m run (sec.) the average of 3.8±0.4 for football and 3, 7±0.5 for futsal. It is concluded that they presented very approximate results and suggest that there was no significant difference. It is suggested that new studies be carried out. Keywords: Futsal. Field Football. Physical Capabilities.